Implementasi Pembelajaran Entrepreneurial dalam Pendidikan Seni Rupa - Pranata, Moeljadi (citeus, 2017)
This study aims to develop a model of entrepreneurial learning in the field of art education in secondary schools. For this purpose, teachers have developed textbooks designed in accordance with the entrepreneurial learning cycle. The study found that art education teaching materials, designed according to specific learning strategies, have the potential to improve learners' entrepreneurial mindset. The results of this study offer strategic value for the development of entrepreneurship education in Indonesia, particularly considering that the findings have the potential to be extended to other fields and subjects across various types and levels of education.